2019
DOI: 10.1016/j.coemr.2018.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory analysis in obesity epidemiology: A promising life course approach

Abstract: The prevalence of obesity has been increasing in the past few decades across the world.[1] This trend is expected to continue owing to the rising pandemic of "Western diet" and sedentary lifestyle in the low and middle-income regions. High body mass index (BMI, the weight in kilograms divided by the square of the height in meters) has been established as a risk factor for numerous chronic diseases, including cardiovascular disease, type 2 diabetes, many cancers, chronic kidney disease, and an array of musculos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…Trajectory modelling can estimate individual trajectories, identify groups of individuals following similar progression over time, estimate group memberships (i.e. within each group, there may be variation in trajectories), as well as identify high-risk groups for targeted intervention (16)(17)(18) . To date, however, there is limited research on the rate of GWG and GWG trajectories (19) and possible associations with birth outcomes (20,21) .…”
mentioning
confidence: 99%
“…Trajectory modelling can estimate individual trajectories, identify groups of individuals following similar progression over time, estimate group memberships (i.e. within each group, there may be variation in trajectories), as well as identify high-risk groups for targeted intervention (16)(17)(18) . To date, however, there is limited research on the rate of GWG and GWG trajectories (19) and possible associations with birth outcomes (20,21) .…”
mentioning
confidence: 99%
“…We provide further evidence for the importance of a life-course approach in public health. Rather than investigating the effects of exposure at a single time point or stage of development, studying the effects of overweight and obesity as a continuous exposure during the life-course might help to better understand the natural history of its association to type 2 diabetes and point towards different causal mechanisms 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Describing the determinants that differentiate these trajectories as well as their association to other health outcomes can aid in the design of more precise and targeted interventions to influence an individual´s health most efficiently 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have begun to assess how weight change over the life course can be predicted and may influence future disease risk. Using GBTM, critical periods of exposure and patterns of weight change can be identified . Pooling two large prospective cohort studies yielding combined data on 409,796 individuals, Petrick et al observed that continued increases in excess weight across the life course, particularly when weight gain begins by early adulthood, is associated with increased risks of esophageal and gastric cardia adenocarcinomas.…”
Section: Question 1: What Is the Evidence Regarding The Importance Ofmentioning
confidence: 99%